A Comparative Study of the Severity Ranking of Risks in the Indian Automobile Manufacturing Supply Chain Using PROMETHEE, VIKOR and TOPSIS - Vinod G. Surange; Sanjay U. Bokade (Vikalpa)
The supply chains in automobile manufacturing face numerous risks, impacting organisational performance due to improvised responses and inadequate contingency plans. This study employs the PROMETHEE methodology to identify and rank critical risk factors (CRFs) in the Indian automotive manufacturing supply chain. Thirteen risks were evaluated across five industry criteria using entropy methodology to ensure a robust and objective assessment of each risk factor. Risks related to delays, management, and suppliers emerged as the most severe. A comparison with VIKOR and TOPSIS methods was conducted. Prioritising risk factors through this approach aids organisations in addressing threats effectively.